Communication of Parents and Early Childhood to Build Confidence in The Pandemic Covid-19 - Eka Aryani (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2021)
Abstract: This study uses qualitative research, with data collection methods using interviews, observation, and documentation. Data analysis techniques using the Speadley model. The data validity technique uses triangulation. This research focuses on parental communication in building self-confidence in early childhood during the co-19 pandemic. Communication is an important requirement for children, especially to increase the confidence of early childhood. Based on research in Margorejo Village, Tempel Subdistrict, from 20 samples obtained a comparison data of 69% of parents applying democratic communication patterns, 31% of parents applying permissive communication patterns, and 29% of parents applying authoritarian communication patterns. Early childhood who have high self confidence comes from parents who implement democratic communication.Komunikasi Orang Tua dan Anak Usia Dini Membangun Keyakinan di tengah Pandemi Covid-19Abstrak: Penelitian ini menggunakan penelitian kualitatif, dengan metode pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Teknik analisis data menggunakan model Speadley. Teknik keabsahan data menggunakan triangulasi. Penelitian ini berfokus pada komunikasi orang tua dalam membangun rasa percaya diri pada anak usia dini di masa pandemi covid-19. Komunikasi merupakan kebutuhan penting bagi anak, terutama untuk meningkatkan kepercayaan diri anak usia dini. Berdasarkan penelitian di Desa Margorejo Kecamatan Tempel, dari 20 sampel diperoleh data perbandingan 69% orang tua menerapkan pola komunikasi demokratis, 31% orang tua menerapkan pola komunikasi permisif, dan 29% orang tua menerapkan pola komunikasi otoriter. Anak usia dini yang memiliki rasa percaya diri yang tinggi berasal dari orang tua yang menerapkan komunikasi demokratis.